Association between mortality and cardiovascular diseases in the vulnerable Mexican population: A cross-sectional retrospective study of the COVID-19 pandemic - Padilla-Rivas, Gerardo R.; Delgado-Gallegos, Juan Luis; Garza-Treviño, Gerardo; Galan-Huerta, Kame A.; G-Buentello, Zuca; Roacho-Pérez, Jorge A.; Santoyo-Suarez, Michelle Giovana; Franco-Villareal, Hector; Leyva-Lopez, Ahidée; Estrada-Rodriguez, Ana E.; Moreno-Cuevas, Jorge E.; Ramos-Jimenez, Javier; et al. (Frontiers in Public Health, 2022)
Cardiovascular diseases (CVD´s) continue as the primary cause of death worldwide. During the past couple of years, and with the surge of the COVID-19 pandemic, deaths linked to CVD´s were -slightly overshadowed by those deaths related to COVID-19, albeit during the highest peaks of the pandemic. The present study derived from understanding the correlation between both diseases, from the standpoint of patients already diagnosed with CVD´s (n = 41883) and what comorbidities had the highest influence on overall patient death (n = 3637). Obesity, hypertension, and diabetes are all linked to worsening the outcome of COVID-19 positive patients, hence they were considered when looking at the overview of all CVD positive patients. Our finding showed that 1697 deaths were related to diabetes (p < 0.001), 987 deaths were related to obesity (p < 0.001), and lastly 2499 deaths were attributed to hyper-tension (p < 0.001) individually. Using logistic regression modeling, we found diabetes (OR: 1.744, p < 0.001) and hypertension (OR: 2.179, p < 0.001) had a high impact on patient deaths. Hence, having a CVD diagnosis, with hypertension and/or diabetes, seems to increase the likelyhood of complication leading to death in COVID-19 positive patients.